IMPLEMENTASI SELF-ASSESSMENT DALAM REFLEKSI PROFESIONAL GURU DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Dwi Saraswati, Risma; Septian Akbar; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of self-assessment in teachers' professional reflection is an important component for improving the quality of education in elementary schools. However, studies on the use of self-assessment as a strategy for teachers' professional reflection remain limited, particularly those addressing the development of classroom management, pedagogical competence, and its integration into the professional development system for teachers in Indonesia. This study aims to analyze the implementation of self-assessment in the professional reflection of elementary school teachers through a Systematic Literature Review (SLR) approach. The research was conducted by analyzing 30 national and international articles relevant to the research topic. Data analysis employed the IMRAD framework (Introduction, Method, Result, and Discussion), which aimed to map the state of the art, research gaps, scientific contributions, methodology, findings, and discussions from previous studies. The results of the review indicate that self-assessment has a positive impact on improving classroom management competence, pedagogical skills, professional reflection, self-efficacy, and the quality of learning. In addition, self-assessment enables teachers to analyze their strengths and weaknesses more objectively, which serves as a basis for continuous professional development. Based on this research, it was found that valid, reliable, and contextually appropriate self-assessment instruments for elementary school teachers in Indonesia are still limited. Therefore, the researchers recommend integrating self-assessment into the Teacher Performance Appraisal (PKG) system, teacher induction programs, and the strengthening of professional reflection practices through Teacher Working Groups (KKG) to support a reflective learning culture and the sustainable improvement of educational quality.